Validity Analysis of the Science Learning Tools using OrDeP2E Models with Contextual Approaches to Improve Creative Thinking Skills of Junior High School Students - Hamsa Doa; Richardo Barry Astro; Konstantinus Denny Pareira Meke (Jurnal Pendidikan Fisika, 2020)
The OrDeP2E learning model based on a contextual approach is a science learning activity based on a contextual approach that emphasizes the creative thinking process of junior high school students. The syntax of the OrDeP2E learning model stands for: 1) Problem definition, 2) Problem Orientation, 3) Hypothesis Submission, 4) Hypothesis Testing, and 5) Evaluation. This study aims to obtain the OrDeP2E model of natural science learning tools with a contextual approach that is appropriate for improving the creative thinking of junior high school students. This study refers to the development of the 4-D model. The results showed that the development of natural science learning tools are suitable to be applied in science learning with the following results: the syllabus got a score as many as 3,45 (valid), the implementation plan of learning got a score as many as 3,53 (valid), teaching material got a score as many as 3,50 (valid), student worksheets get a score as many as 3,63 (valid), creative thinking skills test get a score as many as 3,55 (valid).